An Existential Reading of Family Ties - Jahan, Israt (EAST WEST JOURNAL OF HUMANITIES, 2015)
Examining different characters of Family Ties (Lispector, 1972), the present paper aims at demonstrating Clarice Lispector’s projection of ties at various different levels often starting with family ties, stretching between individuals, objects, and natural world and then untying or losing previously existing ties. The paper highlights the attention she pays to the anxiety concerning all the disturbances of the body and the mind that has been so long denied. Through the research it is shown how her different characters respond to the cultivation of self, and bestows prominent attention to self-respect resulting from self-doubt. Her experimentations with female characters are not confined to the conflict of male and female; rather it continues with multifarious themes which find their abode in her collection of thirteen short stories entitled Lacos de Familia (Family Ties) where she writes about human suffering and failure, the disarray of humanity, human’s total awareness of inevitable alienation and the pressing need to overcome danger, and the most forcefully of all, encountering ultimate nothingness. Influenced by existentialist writers, Lispector illuminates the conflict between public and private self, and magnifies the terror upon realizing the failure of language to communicate; that results into the use of different tools of language to find a rescue (Pontiero, 1972. p. 134). Though the existential struggle of the characters consists of series of paradoxes with no solution, the paper will discuss the steps they have taken and the time they have passed through.